2023
DOI: 10.3389/fmicb.2023.1164904
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between plants and epiphytic lactic acid bacteria that affect plant silage fermentation

Abstract: Lactic acid bacteria (LAB) have the ability to ferment water-soluble carbohydrates, resulting in the production of significant amounts of lactic acid. When utilized as additives in silage fermentation and feed, they have been shown to enhance the quality of these products. Epiphytic LAB of plants play a major role in the fermentation of silage plants. Plant species in turn affect the community structure of epiphytic LAB. In recent years, an increasing number of studies have suggested that epiphytic LAB are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…In general, LAB are common inoculants used for ensiling feedstock ( Muck et al., 2018 ; Mu et al., 2020 ; Yang et al., 2021 ). They can rapidly lower the pH of ensiled materials and improve fermentation quality ( Chen et al., 2023 ). However, in recent years, studies found that due to their ability to produce cellulases, hemicellulases, and amylases, B. spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, LAB are common inoculants used for ensiling feedstock ( Muck et al., 2018 ; Mu et al., 2020 ; Yang et al., 2021 ). They can rapidly lower the pH of ensiled materials and improve fermentation quality ( Chen et al., 2023 ). However, in recent years, studies found that due to their ability to produce cellulases, hemicellulases, and amylases, B. spp.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the additives, microbial inoculants are the most extensively utilized primarily by LAB. These inoculants can swiftly reduce silage pH by rapid proliferation during the initial ensiling phase, suppressing deleterious acid-intolerant microbes and yielding superior quality silage ( Carvalho et al., 2021 ; Chen et al., 2023 ). Nascimento Agarussi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the additives, microbial inoculants are the most extensively utilized primarily by LAB. These inoculants can swiftly reduce silage pH by rapid proliferation during the initial ensiling phase, suppressing deleterious acid-intolerant microbes and yielding superior quality silage (Carvalho et al, 2021;Chen et al, 2023). Nascimento Agarussi et al (2019) used Lactobacillus plantarum and Pediococcus pentosaceus to ensile alfalfa and found that both LAB were able to enhance the fermentation quality of the silage feed.…”
Section: Discussionmentioning
confidence: 99%
“…With the widely application of plant essential oils, their effects on improving the silage quality have been studied. Chen et al (2023) reviewed the effects of essential oils and their activity on inhibiting bacteria and fungi, and explored the contribution of plant essential oils to silage quality, and provided some knowledge to the application and development of plant essential oils as feed additives in silage production. They found that plant essential oils can inhibit the growth and activity of various harmful microorganisms in silages whereby their ability to affect the permeability of cell membrane, ATPase activity and cell division, and limit biofilm formation.…”
mentioning
confidence: 99%
“…However, the lack of adequate epiphytic LAB is one of the reasons for the difficult ensiling of mulberry (He et al, 2020 ); inoculated commercial or isolated LAB could solve this problem (Pitiwittayakul et al, 2021 ). Usually, epiphytic LABs are more effective than commercial inoculants due to the efficiency of carbohydrate utilization and adaptation to the environment (Chen et al, 2023 ). In addition, many LABs (such as Lactobacillus helveticus Li et al, 2019 , Lactobacillus sanfranciscensis , and Lactobacillus farciminis Galli et al, 2018 ) exhibited excellent antioxidant capacity, which enables the production of antioxidant enzymes, such as superoxide dismutase (SOD) and catalase (CAT), to neutralize or alleviate reactive oxygen species (Vougiouklaki et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%